2022
DOI: 10.1111/jfpe.14116
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of thermodynamic performance of microwave dryer of onion

Abstract: The present study was designed for the experimental and modeling investigations on thermodynamic analysis of drying onion slices using four microwave power levels (100, 350, 500, and 750 W) and the four samples thicknesses (2.5, 5, 7.5, and 10 mm). A multilayer feedforward artificial neural network was employed in order to predict energy and exergy performance of the dryer and the prediction success were compared using three evaluation criteria. The average values for energy efficiency and specific energy loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…These cracks caused a volume change, further accelerating the removal of moisture and declining the D t , which in turn enhanced the E ef [6]. The increment in the E ef by raising the MP and reducing the ST was reported before [8,55]. On the other hand, a comparison of the various pretreatments showed that the highest E ef was achieved in the blanching pretreatments while the untreated samples exhibited the lowest E ef .…”
Section: Energy Efficiency (E Ef )mentioning
confidence: 90%
“…These cracks caused a volume change, further accelerating the removal of moisture and declining the D t , which in turn enhanced the E ef [6]. The increment in the E ef by raising the MP and reducing the ST was reported before [8,55]. On the other hand, a comparison of the various pretreatments showed that the highest E ef was achieved in the blanching pretreatments while the untreated samples exhibited the lowest E ef .…”
Section: Energy Efficiency (E Ef )mentioning
confidence: 90%